EALLU Abridged Edition 2018 - Sustainable Development Working Group (SDWG) (Arctic Council Secretariat, 2018)
This is the 2nd abridged edition of the original Eallu cookbook which was released as a deliverable at the 2017 Fairbanks Ministerial meeting of the Arctic Council. This is a book about the fabulous abundance and diversity of food in the Arctic. While many think of the Arctic as a place of climatic extremes and scarcity, in fact the Arctic hosts an extraordinary food culture, built on 10,000 years of knowledge, and intergenerational knowledge transfer.